Determination of a maintenance strategy for machinery systems of autonomous ships. (15th December 2022) - Karatuğ, Çağlar; Arslanoğlu, Yasin; Guedes Soares, C.
Abstract: This paper proposes a hybrid multi-criteria decision-making approach to determine the best maintenance strategy for the machinery systems in autonomous ships of different levels of autonomy. The proposed methodology includes the Analytic Hierarchy Process to identify criteria weighting and the Technique for Order of Preference by Similarity to Ideal Solution to determine the best maintenance alternative. A sensitivity analysis is conducted to determine the impact of criterion weighting on the calculated rank scores and to reveal the criticality of the criteria. The study presents and considers various hybrid maintenance strategies for autonomous ship concepts as possible maintenance alternatives. The selection of the maintenance policy that combines condition-based and time-based approaches for 3rd and 4th levels of ship autonomy, as the best maintenance alternative, demonstrates the basic idea of the study. In addition, the key findings of the paper ensure crucial insights to the maritime industry in the decision-making process on the maintenance strategy that can be adapted to different types of autonomous ship concepts. Highlights: A multi-criteria decision-making approach is used to determine the maintenance for the machinery systems in autonomous ships. The methodology includes the AHP to identify criteria weighting and the TOPSIS to determine the best maintenance alternative. A sensitivity analysis is conducted to determine the impact of criterion weighting on the calculated rank scores. The policy that combines condition-based and time-based approaches for 3rd and 4th levels of ship autonomy, was chosen. The findings of the paper ensure crucial insights on the maintenance strategy to be adapted to different levels of autonomy.